Writing the political philosophy paper: threshold concepts and troublesome knowledge - Siddiqui, Asif (My University, 2014)
Topics: motivation, threshold concepts, and application to position paper in political philosophy.
Presented on February 8, 2014 at the American Political Science Association (APSA) Teaching and Learning Conference held at the Sheraton Society Hill in Philadelphia, United States.
Keywords: threshold concepts